2014
DOI: 10.2337/dc14-0908
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Severe Hypoglycemia, Adverse Macrovascular Events, and Inflammation in the Edinburgh Type 2 Diabetes Study

Abstract: OBJECTIVETo determine whether a history of severe hypoglycemia was associated with an increased risk of subsequent macrovascular events in people with type 2 diabetes and to explore possible mediation of this association by inflammation. RESEARCH DESIGN AND METHODSA cohort of 1,066 adults aged 60-75 years with type 2 diabetes was evaluated prospectively. Baseline history of severe hypoglycemia and plasma levels of the inflammatory markers C-reactive protein, fibrinogen, interleukin-6, and tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 37 publications
3
49
0
5
Order By: Relevance
“…Moreover, several studies have demonstrated or reported that acute hyperglycemia (5, 6, 9, 23, 27) or hypoglycemia (7, 25, 32, 41) can result in increased atherothrombotic mechanisms, reduced fibrinolytic balance, and impaired endothelial function in both nondiabetic and diabetic individuals (6, 10, 25, 32, 37). Despite recent data reporting the acute effects of hyperglycemia and hypoglycemia on pro-atherothrombotic responses, only one study has compared their relative effects in humans (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated or reported that acute hyperglycemia (5, 6, 9, 23, 27) or hypoglycemia (7, 25, 32, 41) can result in increased atherothrombotic mechanisms, reduced fibrinolytic balance, and impaired endothelial function in both nondiabetic and diabetic individuals (6, 10, 25, 32, 37). Despite recent data reporting the acute effects of hyperglycemia and hypoglycemia on pro-atherothrombotic responses, only one study has compared their relative effects in humans (9).…”
Section: Introductionmentioning
confidence: 99%
“…Во время гипогликемии повышается уровень цирку-лирующих воспалительных маркеров, таких как CD40, CD40-лиганд, интерлейкин-6, С-реактивный белок, а также маркеров окислительного стресса, провоспали-тельных и атеротромботических биомаркеров (ICAM-1, VCAM-1, E-селектин, VEGF, ФНО-α) [21]. Эндотелиальная дисфункция является ранним предиктором субклиниче-ского атеросклероза.…”
Section: потенциальные механизмы влияния гипогликемии на сердечнососunclassified
“…Течение СД часто осложняется высоким риском воз-никновения гипогликемии, которая является значимым предиктором кардиоваскулярных событий, неблагопри-ятных клинических исходов и смертности у пациентов с СД 2-го типа [3][4][5][6]. По данным Connelly K.A.…”
unclassified
“…57, 58 A recent systematic review and meta analysis, as well as cohort studies, have proved that severe hypoglycemia is associated with increased risk of cardiovascular disease and death among patients with type 2 diabetes. [59][60][61][62] Regarding patients with type 1 diabetes, it is suggested that repeated hy poglycemia could be related to worse prognosis in terms of preclinical atherosclerosis, as well as considered an aggravating factor for it. [63][64][65] Only a few studies have examined whether hypoglyce mia may increase the risk of cardiovascular dis ease or death among patients with type 1 diabe tes, and the results were ambiguous.…”
mentioning
confidence: 99%